Analisis Kasus Wanprestasi Antara Debitur Dan Kreditur Terhadap Perjanjian Pinjaman Kredit Bank Studi Kasus Putusan (Nomor 5/PDT.G.S/2023/PN.BTG) - Trianda Lestari; Syahrando Muhti; Muhamad Fatur Rahman Bey Husdi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
A broken promise or default is a situation where a debtor is unable to fulfill his obligations in accordance with the debt and receivable agreement he made, for example not making installments or repayment on time. As in article 13138 of the Civil Code which states